Holly Sacrament: the medicine of spiritual immortality or a vehicle for contamination? - Dimitrios Anyfantakis (Medicinski glasnik, 2021)
The Holy Communion is the oldest Christian practice, through which a gathered group of people partake bread and wine with a shared spoon. The pandemic of COVID-19 produced unexpected social instability and chaos. In Greece, a recent bishop’s death from COVID-19 re-awaked the issue of infection transmission by using a common chalice and spoon. This review evaluates the available medical literature on this topic from the beginning of the pandemic until today.
Keywords: COVID-19; Eastern Orthodoxy; infections